2020
DOI: 10.1016/j.jobcr.2020.03.010
|View full text |Cite
|
Sign up to set email alerts
|

No age predilection for a disease like OSMF. A case report of 5-year-old child

Abstract: Background: Oral Sub Mucous Fibrosis (OSMF) is a clinical entity, well known since the time of Sushruta as 'Vidari'. OSMF is a chronic subtle disease that is associated with significant functional morbidity and an increased risk for malignancy. Generally, OSMF is considered as an adult disease, but recently Indian suburb area has reported incidence of 0.2-1.2 percent in pediatric age group as well. The pathogenesis of the disease is not well established, but is believed to be multifactorial. Areca nut chewing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“… 7 Jain et al 1 had conducted a review in 2019 with cases below 10 years of age and presented with a protocol for management of this premalignant condition in paediatric population. Talla et al 8 and Kariya et al 9 both reported a case of OSF in 5-year-old child. Recently, More et al 10 conducted an analysis of 36 cases of OSF in the paediatric population.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Jain et al 1 had conducted a review in 2019 with cases below 10 years of age and presented with a protocol for management of this premalignant condition in paediatric population. Talla et al 8 and Kariya et al 9 both reported a case of OSF in 5-year-old child. Recently, More et al 10 conducted an analysis of 36 cases of OSF in the paediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…OSF affects people of all ages, however, it is more common in adults between the decade of 2 to 4 and slightly more frequently in females than in males 5 , 7 . It begins gradually and often lasts between 2 to 5 years but several cases with sudden onset and different periods have been reported 8 .…”
Section: Introductionmentioning
confidence: 99%
“… 2 It is characterized by reduced movement and depapillation of the tongue, blanching and leathery texture of mucosa, trismus, and inability to eat, associated with the formation of vesicle due to juxtaepithelial inflammatory reaction followed by fibroelastic changes in lamina propria and epithelial atrophy. 3 The prevalence of OSMF in the Indian subcontinent has been estimated to range from 0.2 to 2.3% in males and 1.2 to 4.6% in females, with a broad age range from 11 to 60 years. 4 In recent years, there is an increased prevalence of OSMF in the younger population mainly due to household environment, peer pressure, and attractive pouches of areca nut products.…”
Section: Introductionmentioning
confidence: 99%